China's Health Diplomacy Strategy During COVID-19 Crisis 2020-2022 - Kartodirdjo, Azzizah; Rahman, Muhammad Sigit Andhi (Laboratorium Hubungan Internasional, FISIP, Universitas Jenderal Soedirman, 2024)
In time of crisis like COVID-19 outbreak, China’s health diplomacy has become a spotlight in terms of its international momentum in dealing the virus. This research is important to know how health diplomacy can be used as an effective foreign policy. The research question in this paper asks how did China conduct health diplomacy during the COVID-19 crisis from 2020 to 2022. This research used descriptive and literature research methods by collecting secondary data from related research and international organization, WHO, as main source for COVID-19 data. The data were analyzed using neoclassical realism theory. Not to mention, there is not much literature that analyzes China's before until the recent